Intellectual capital as a tool for achieving competitiveness: Vision and analysis - Mahdadi, Loubna; Zeguieb, Kheira; Redjem, Khaled (International journal of economic perspectives, 2025)
This study aims to highlight the role of intellectual capital in achieving competitiveness for organizations. The subject was studied by clarifying the conceptual framework of intellectual capital as well as the competitiveness achieved in the organization and integrating the relationship between intellectual capital and competitiveness through the general vision of the subject and its in-depth analysis. Previous studies on the subject were relied upon, as the first axis related to the theoretical framework of intellectual capital - creativity and competitiveness - was addressed. The study concluded that there is an integrated relationship between intellectual capital and competitiveness, as intellectual capital contributes to helping the organization achieve efficiencies as well as creativity and innovation that enable it to create value and achieve its goals to confront its competitors.